Transarterial chemoembolization combined with sorafenib and iodine-125 seed brachytherapy for hepatocellular carcinoma with portal vein tumor thrombus: a retrospective controlled study. Issue 1 (5th January 2022) - Huang, Jingjun; Cai, Mingyue; Huang, Wensou; Guo, Yongjian; Zhou, Jingwen; Liang, Licong; Lin, Liteng; Zhou, Zhimei; Lian, Hui; He, Mingji; Zhu, Kangshun
Abstract : Supplemental Digital Content is available in the text